Aesthetic Dermatology Training During Residency: Do we Need to Revise the Postgraduate Curriculum? - Suchana Marahatta; Deeptara Pathak Thapa (Nepal Journal of Dermatology, Venereology & Leprology)
Aesthetic Dermatology (AD) is a growing sub-unit of dermatology. Appearance plays a vital role in enhancing and boosting self-confidence. Reports are showing a growing demand for AD throughout the world. To converge this increasing demand, we must pivot on engendering certified competent dermatologists and hence include this sub-specialty in the dermatology residency program.